PREVALENCE OF GASTROINTESTINAL DISEASES IN SURKHANDARYA REGION - Baxtiyor Xolnazarovich Shoymardonov; Guli Islamovna Shaykhova (The Conference Hub, 2025)
Gastrointestinal diseases are among the most widespread illnesses across different regions of the world. In such conditions, in order to prevent a negative impact on human life expectancy, it is advisable to implement and expand modern diagnostic capabilities for early detection and to prevent the emergence of various factors contributing to the spread of these diseases.